Antioxidant properties of mango, guava and papaya peel extracts and their effects on the stability, physicochemical properties and acceptability of frozen beef burger / Marina Zulkifli - Zulkifli, Marina (2010)
This study was undertaken to investigate the potential of fruit waste materials as sources of natural antioxidants. The fruit peels including mango, guava and papaya peel were extracted using water. The brine shrimp lethality assay indicated that the extracts were non-toxic . Phytochemical screening was also evaluated and the experimental data showed that the extracts contained alkaloid , saponins, triterpene and steroid. The total phenolic content (TPC) was determined by folin-ciocalteu assay while antioxidant activities were determined by using ferric reducing antioxidant power (FRAP), 2,2diphenyl- l-picrylhydrazyl (DPPH) free radical scavenging, ferric thiocyante (FTC) and thiobarbituric acid (TBA) assays. These antioxidant activities were compared to synthetic antioxidants, BHA/BHT combination and ascorbic acid. The results demonstrated that TPC varied from 3.23 to 15.84 g OAE/lOO g. Mango peels extract (MPE) exhibited the highest total phenolic content compared to guava peel extract (OPE) and papaya peel extract (PPE). In the FRAP assay, the MPE at 200 ppm, as well as OPE at 400 ppm and PPE at 1200 ppm, exhibited reducing power comparable to 200 ppm of BHA/BHT. At concentration of 250 ug/ml, the DPPH radical scavenging activity of extracts and standards decreased significantly in the order of MPE > OPE > BHA/BHT > ascorbic acid > PPE. For the FTC assay, the antioxidant activity of MPE was significantly higher than ascorbic acid, OPE and PPE but lower than BHA/BHT while in the TBA assay , the percentage inhibition of BHA/BHT and ascorbic acid were higher than the extracts. The quantitative analysis for flavonoids showed the presence of catechin , epicatechin and kaempferol in the extracts. Further study was conducted to evaluate the antioxidative effect of the extracts on the stability of beef burger during 4 months of frozen storage. Five formulations which consist of control (sample without antioxidant) (Fl), sample with addition of 200 ppm MPE (F2), sample with addition of 400 ppm OPE (F3), sample with addition of 1200 ppm PPE (F4) and sample with addition of 200 ppm BHA/BHT (F5) were prepared . Peroxide value (PY) and thiobarbituric acid (TBA) test were performed and the results showed that the PY and TBA values of F5 exhibited the lowest values followed by F2, F3, F4 and Fl. The physico-chemical analysis demonstrated that addition of MPE could increased the stability of red colour (a* value) and water holding capacity , and reduced the firmness of beef burger as compared to control sample. The sensory scores of beef burgers were unaffected by addition of the extracts. Hence the plant by-product such as mango peel possessed a potential source as natural food antioxidant which can be incorporated into the food product such as beef burger and extended the shelf life of the product.